Performance enhancement of FSO link with RIS-aided over Weibull distribution for 5G/6G and IoT applications - Duong Huu Ai; Van Loi Nguyen; Hoang Huu Duc; Khanh Ty Luong; Viet Truong Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
With continuous development of wireless communication and internet of things (IoT) technology enables many terminals to be interconnected with each other through the external environment by wireless communication. Along with that, 5G/6G technology provides services with enhanced quality and high data transmission speeds, requiring the implementation of IoT in the 5G/6G architecture. Free space optical (FSO) communication is considered as a promising technique that can connect IoT devices by high-speed communication link, so for wireless networks to fully realize the potential of 5G/6G technology providing speeds of 100 Gb/s or more, FSO is the optimal choice. By implementing FSO features in IoT, the performance and convegare of IoT will be improved and enhanced by using techniquaes for FSO systems. Therefore, this paper proposed and investigated the FSO communication system using reconfigurable intelligent surfaces (RISs) over Weibull distribution. The performance of system is evaluated according to the average channel capacity (ACC) parameters in the case with and without RIS, while the the different of the model is changed. The average spectral efficiency (ASE) parameters can also be represented ACC.